2014
DOI: 10.30638/eemj.2014.279
|View full text |Cite
|
Sign up to set email alerts
|

Technological Posture and Corporate Social Responsibility: Effects on Innovation Performance

Abstract: Interest in the relationship between innovation and Corporate Social Responsibility (CSR) has grown considerably in the last few years. The aim of this paper is to analyze the relationship between a company's technological posture and CSR, as one of the main determinants of technological innovation performance. From knowledge-based and stakeholders' theories a structural equations model of relationships was established and statistically tested through Smart PLS on a sample of Spanish firms from the renewable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…CSR is also a tool to differentiate a firm from other firms. Most studies emphasize that when CSR is included in a corporate strategy, it tends to enhance technological innovation investment [49,50]. However, the reverse direction of how innovation imposes on a firm's decision to take part in CSR is hardly examined [51].…”
Section: Innovation and Corporate Social Responsibilitymentioning
confidence: 99%
“…CSR is also a tool to differentiate a firm from other firms. Most studies emphasize that when CSR is included in a corporate strategy, it tends to enhance technological innovation investment [49,50]. However, the reverse direction of how innovation imposes on a firm's decision to take part in CSR is hardly examined [51].…”
Section: Innovation and Corporate Social Responsibilitymentioning
confidence: 99%
“…The companies can communicate this knowledge and information in processes of technological capability [45]. However, most authors believe in the positive effect of CEP on technological capability investment [46,47]. Moreover, various stakeholders have different interests in companies [48].…”
Section: Corporate Environmental Performance (Cep) and Technological mentioning
confidence: 99%
“…Flammer [3] considers that environmentally friendly responsible experience of companies can increase the technological capability and stock prices, where those behaving environmentally unfriendly activities can face a significant decrease in its share price and capabilities. However, most authors believe in the positive effect of CEP on technological capability investment [46,47]. Moreover, firms with higher technological capability investments would generally pay more importance to their CEP activities and finally increase their financial performance [61].…”
Section: The Mediating Effect Of Technology Capabilitymentioning
confidence: 99%
“…Nevertheless, there is a general opinion according to which corporate social responsibility (CSR) should be integrated into the general strategy of an organization in order to consistently improve their ESG performance, its image and reputation, obtain some competitive advantages, and for reaching a high level of financial performance, thus generating sustainable benefits for both the company and the society [43][44][45][46][47][48][49][50]. Additionally, some researchers have demonstrated that CSR activities are indissolubly linked to innovation-the more an organization is involved in CSR activities, the higher the chances for it to obtain a plus of innovation which derives from the exploitation of the knowledge of the interested parties and the pressures made by them [38,[50][51][52].…”
Section: Literature Reviewmentioning
confidence: 99%